STRUKTUR PASAR MINYAK KAYU PUTIH (MELALEUCA LEUCADENDRON OIL) (Studi Kasus di Kecamatan Namlea Kabupaten Buru–Maluku) - Silvana Maulidah (Jurnal Manajemen Pemasaran, 2010)
In Indonesia, Melaleuca leucadendron Oil is only produced in several regions, including the District of Buru, Ambon, Seram, New Guinea, Java, and Borneo. This condition is a good opportunity to develop Agro Oil White Wood, White Wood Oil Agro-industry presence in the operations must be taken to ensure that producers are able to survive in a market situation that took place, so hopefully will create an effective and efficient market. This study aims to analyze the structure of eucalyptus oil agro-industry market. Determiningthe location of the research done by purposive (deliberately) that is in the Regency of Buru as the largest producer of eucalyptus plants in the Moluccas. Data analysis methods used were qualitative (descriptive) and quantitative analysis. Descriptive analysis is used in the determination of market structure include the degree of product differentiation, barriers to market entry, and the level of market knowledge and determination of market behavior including pricing policies, institutional system of market and marketing functions. The quantitative analysis used to determine the degree of market concentration that is measured market share. The results of this study indicate that the market structure of Melaleuca leucadendron Oil agro-industry in the regency of Buru including in markets characterized by monopolistic competition there are many sellers in the market with the same basic product but have been differentiated. From the results of existing research suggested that Melaleuca leucadendron Oil industry need to consider the market structure in determining the price. Melaleuca leucadendron Oil agro need to increase production and marketing activities by creating the uniqueness of the diversification of products so that manufacturers can increase revenue and avoid market saturation.